PENCIPTAAN MANUSIA DALAM PENAFSIRAN AMINA WADUD TERKAIT SURAH AL-NISA AYAT 1 PERSPEKTIF GADAMER - Andre Septian; Rahmi Afriani (Yayasan Baitul Hikmah al-Zain, 2026)
This study examines Amina Wadud's interpretation of Surah al-Nisa verse 1 using Hans Georg Gadamer's hermeneutic perspective. The verse talks about the creation of humans from a nafs and from it zawj was created, in the interpretation of classical scholars it is often understood as unequal validation, with the assumption that men (Adam) are the first humans and women are created from him (Eve). Amina Wadud does not accept this understanding and emphasizes that the creation of humans (men and women) comes from the same essence, namely equality in nature. Using Gadamer's theoretical perspective, we will see from the awareness of historical influence, pre-understanding, combining horizons, and applications. This study explains that Wadud's interpretation is collaborative and contextual. This interpretation provides productive interaction between the text of the Qur'an and the historical reality of Muslim women and presents a more just and inclusive theological structure. This study explains that with Gadamer's hermeneutic perspective, the Qur'an can be interpreted more appropriately with the demands of contemporary ethics without losing the substance of its original message.